Human challenges of global society: a dialogue with Santiago Kovadloff (Cultura Económica, 2019)
We offer our readers the interview conducted by Carlos Hoevel, director of the journal, to the acknowledged Argentine intellectual Santiago Kovadloff. The dialogue took place last year and is focused on the issues that frame the current global situation. The exhaustion of nature, the transformation of citizens into costumers, the problem of the domain of the unknown, the crisis in the relationship with the other, are, among others, the difficulties and challenges that Kovadloff sees in the immediate future of humanity.
Keywords: transformation of subjectivity; exhausted nature; domain; democracy; responsibility